Open innovation and IPRs: Mutually incompatible or complementary institutions? - Mário Alexandre Patricio Martins da Silva (Journal of Innovation & Knowledge (JIK), 2019)
In this paper, we explain the analytics of a particular type of mechanism of open innovation (OI), namely the management of non-pecuniary exchange of information, and address the relationship between intellectual property rights (IPRs), particularly patent rights, and OI using a static game-theoretic setting of research and development (R&D) competition. We develop a duopoly model in which for-profit firms can contribute to downstream improvements to be made by a diverse community of inventors, workers and users of technology by creating knowledge spillovers which the development community employs as an input for its innovative efforts. Although a money market for R&D information does not exist, the commercial firms may appropriate an indirect return on innovative efforts. The degree of spillover information is determined endogenously, and equilibria with voluntary revealing may arise in our theoretical model. We show that, surprisingly perhaps, a rise in the strength of patent protection induces the free sharing and dissemination of technological information and other contributions to the OI development of innovations. Conversely, a fall in the strength of the patent system induces the exercise of traditional IPRs by innovative firms to protect their intellectual assets.
Keywords: O33; 650; Open innovation; IPRs; Knowledge spillovers; R&D